INSOLITO CASO DE SUPERPARASITISMO EN TAQUINIDOS - Bobadilla G., Dante (Acta Entomológica Chilena, 2022)
A rather unusual case of "superparasitism" by a Tachinid fly (Díptera), Euphorocera peruviana Townsend, 1912, upon a full grown larvae of Melipotis sp. (Lepidoptera: Noctuidae) is reported in this paper, showing an extraordinary over-oviposition of 148 macro-eggs of the parasitoid on the dorsal dermis of the host larvae, none of which obviously yielded a single adult imago of the fully developed fly. The examined samples were collected January 1992 at the Mesquite forest (Prosopis spp.) in the Pampa above Iquique (I Región, Chile) at 1.000 m altitude.